2018
DOI: 10.3390/su10020356
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Quantifying User Acceptance of Personalized Business Modes Based on TAM, Trust and Attitude

Abstract: Abstract:With the rapid development of economics and social businesses, users' business demand has changed a lot. More and more people want to personalize their business modes so that they can get better experiences in business and learning activities. The key factor of personalized business mode is to consider users' individual needs on business activities, so that users can receive differentiated services. Users' satisfaction on personalized services will effectively improve the consuming experience of users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 41 publications
4
40
1
1
Order By: Relevance
“…This result is consistent with the previous findings of technology acceptance studies in which usage intentions have been found to be significantly related to attitudes. In other words, the attitudes had positive effects on usage intentions [56], and the findings were consistent in studies such as Zhu et al [23], Pookulangara and Koesler [24], Dai et al [25], Kumar and Mukherjee [26], Zhao et al [27], and Limpf and Voorveld [28]. Moreover, LBS usage intentions may be examined from theoretical approaches by way of the TAB to provide deeper insight into the attitudes and behaviors of LBS users.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This result is consistent with the previous findings of technology acceptance studies in which usage intentions have been found to be significantly related to attitudes. In other words, the attitudes had positive effects on usage intentions [56], and the findings were consistent in studies such as Zhu et al [23], Pookulangara and Koesler [24], Dai et al [25], Kumar and Mukherjee [26], Zhao et al [27], and Limpf and Voorveld [28]. Moreover, LBS usage intentions may be examined from theoretical approaches by way of the TAB to provide deeper insight into the attitudes and behaviors of LBS users.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, various TAB studies have been used in a number of field studies, including studies of factors related to the usage intentions of online consumers [23], the willingness of consumers to use mobile commerce [24], consumer usage intentions in the context of social media [25], consumer usage intentions for mobile devices [26], and user usage intentions regarding personalized business modes [27]. According to TAB, the use of technology is determined by people's behavioral intentions, which are determined by their attitudes toward technology.…”
Section: Technology Acceptancementioning
confidence: 99%
“…Second, because users' decision-making behavior could be impacted by other factors, future work can be focused on other possible factors, such as users' income and education background, review volume or variance, and users' online experience. Finally, it is also worth to study other research models [62] on user acceptance and consider online reviews within the community context [63].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent survey [1], over 90% of Europeans are using social-network sites. Owing to the advantages of social networks, many companies have integrated social networks into innovation of business modes [2]. For instance, Coca-Cola developed "Lyrics Bottle" [3], which is a social-network application.…”
Section: Introductionmentioning
confidence: 99%
“…(1) What factors influence user willingness toward knowledge sharing in social networks? (2) How do these factors impact user willingness toward knowledge sharing in social networks? Knowledge sharing is helpful for organizations and enterprises to improve their knowledge management and learning innovation.…”
Section: Introductionmentioning
confidence: 99%